KOMITMEN ORGANISASI, KEPUASAN KERJA DAN PRESTASI KERJA DALAM KALANGAN PENSYARAH UNIVERSITI DI KOTA BATAM INDONESIA - Hazriyanto; Ibrahim, Badaruddin (Online Journal for TVET Practitioners, 2018)
University is a place to improve the quality of human resources. The development of university level education in Indonesia, particularly in Batam has involved various parties. They are lectures, university, community and other educational organizations. Most of the studies on commitment, job satisfaction and job performance generally performed in industrial and business sector. Lecturer is one of the important aspects of an educational system in higher education. The objective of this study is to investigate the university organizational commitment, lectures’ job satisfaction and lectures’ performance. Data was collected through questionnaire which involved 179 samples from three university lecturers in Batam, Indonesia including Putera Batam University, Batam University and Riau Kepulauan University. This research utilized SPSS statistical software to analyze the data. The results shows positive and significant relationship among i) commitment and job performance, ii) commitment and job satisfaction, iii) job satisfaction and job performance, and iv) commitment and job satisfaction on job performance. The findings can be used as a reference for the needs of institutions, academics and practitioners in making the standard of evaluation in measuring the university organization and individual staff commitment as well as their performance.